Measurement and Motivations of Earnings Management: A Critical Perspective - Khaled Aljifri (Journal of Accounting, Business and Management (JABM), 2007)
This paper presents a critical perspective of earnings management literature and its measurement and motivations. The paper focuses on accrual-based accounting choices, considered as a well-established tool to manage earnings. It suggests that the accrual-based models used in the literature to measure earnings management are complicated by the difficulty of measuring discretionary and non-discretionary accruals. This raises an important question which is: Are the results related to the earnings management studies accurate and reliable? The paper also highlights a number of complex and interrelated incentives for companies to manage their reported earnings. It is hoped that this study will provide a better understanding of the relationship among discretionary accruals, managerial motivations, and earnings management. Such insights may change the view of insiders and outsiders on the contents of financial statements and the role of auditors. By doing this, the quality of information that is available to the public may be enhanced; and hence, users of annual reports may be better served. Finally, this study may be used as a guide by which financial analysts and other interested parties can evaluate the accuracy and reliability of conclusions related to earnings management.